PEMBUATAN DAN KARAKTERISASI KOMPOSIT LiBOB/MgCl2 DENGAN METODE SOLID STATE REACTION - Darwis, Arwin; Iswadi, Iswadi; Sahara, Sahara (Universitas Islam Negeri Alauddin Makassar, 2019)
The manufacture and characterization of the lithium bus Composite (oxalate) borate with the addition of magnesium chloride (LiBOB/MgCl2). Electrolytes as a media transfer ion battery, plays an important role in the charge-discharge process of lithium ion batteries. The basic ingredients used in the study are lithium hydroxide (LIOH), Borid acid (H3BO3), Our acid dehydrate (H2C2O4 • 2H2O) and magnesium chloride hexahydrate (MgCl2 • 6H2O). The method used in this research is solid state reaction or known as solid-solid method. Based on the results of the XRD characterization, shows the peaks of LiBOB experiencing a shift after being added with 2.5%; 5% and 7.5% MgCl2 • 6H2O, in addition it also raises new peaks of magnesium. While the spread of the material is blown the sample appears evenly with the SEM-EDX test, however there are some elements that are experiencing clotting. And the FTIR test showed a change in the frequency of each mass increase of MgCl2 • 6H2O, but did not cause peak changes in each sample. In the EIS test results, obtaining a low electrical conductivity value, due to agglomeration of the material after the addition of elemental magnesium that is ionic. Thus also causes the diffusion of ions to lower.